Adult safeguarding and the Care Act (2014) – the impacts on partnerships and practice. Issue 4 (14th August 2017) - Cooper, Adi; Bruin, Claire
Abstract : Purpose: The purpose of this paper is to look at the impacts on adult safeguarding partnerships and practice over 18 months following the implementation of the Care Act (2014) from the perspectives of an independent Chair of two Safeguarding Adults Boards (SABs) and a senior manager in adult social care in a local authority. They look at the areas of: wellbeing and safety, safeguarding activity and process, changing criteria and definitions, Making Safeguarding Personal, SABs, safeguarding adult reviews and advocacy. Design/methodology/approach: The authors draw together information from published sources, experience and networks. Findings: The paper argues that the impact on adult safeguarding and SABs has been greater than originally envisaged in a range of areas. This appears to be as a result of adult safeguarding having been made statutory, a new framework having been put in place, and added impetus given to a cultural change in adult safeguarding practice. Originality/value: The authors have been engaged in delivering the adult safeguarding elements of the Care Act (2014) and so provide unique insight into the experience of making the changes required to meet the new statutory requirements and achieve the objective of protecting peoples' rights to live in safety, free from abuse or neglect.